Pragmatics Competence of Preschool Age Children - Eti Setiawati; Putri Kumala Dewi (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2018)
Children’s language acquisition begins at the age of one, that is when the child begins to learn to speak. From that age, children have possessed speech act competence. The speech act competence that is obtained by preschool-age children may cover different kinds of speech acts, such as directive, representative, and expressive acts. These speech acts may be realized in language form as one or two words that describe a particular function of speaking. The objectives of this research are (1) to describe the competence of speech act forms of preschool-age children, (2) to describe the competence of speech act functions of preschool-age children, and (3) to describe the competence of speech act types of preschool-age children. This research uses a qualitative research approach with the descriptive method. The research data consists of utterances of preschool-age children that contain speech act forms, functions, and types. The data analysis model uses the interactive model by Miles and Huberman with an approach based on pragmatics theory and ethnography of communication. Research results show that preschool-age children have possessed (1) competence of speech act forms of interrogatives, imperatives, and declaratives of single syllables, single words, and single sentences; (2) competence of speech act functions of asking, ordering, stating, and inviting; and (3) competence of speech act types of directives, representatives, declaratives, and expressives.